Does The Education Influence Self Efficacy in Tuberculosis Patients? : Systematic Review - Fauziah, Ardianti; Zahroh, Chilyatiz; Nadatien, Ima; Hidaayah, Nur (Journal of Applied Nursing and Health, 2024)
Background: Tuberculosis is still a health problem in the world, one of which is in Indonesia, which is ranked third after India and China. Tuberculosis is transmitted through the air and is caused by the bacteria Mycobacterium tuberculosis. This research aims to determine the effect of health education on self-efficacy in pulmonary tuberculosis patients. Methods: The method used in this research is a systematic review with a systematic review (PRISMA) using several journal databases from Google Scholar, Science Direct, and Pubmed from 2019-2024 with the keywords "tuberculosis," "health education," or "self-management,” or “self-efficacy.” 10 articles ready for review 10 articles obtained with PRISMA Results: The results of a systematic review study show that providing health education influences self-efficacy in pulmonary tuberculosis patients. Conclusion: It is hoped that health education will increase knowledge so that it will change individuals' mindsets so that they have high self-confidence and good health behavior to control their disease, one of which is by obediently taking medication